Virtual Assistant 2021
DOI: 10.5772/intechopen.95242
|View full text |Cite
|
Sign up to set email alerts
|

Specific Wear Rate Modeling of Polytetraflouroethylene Composites via Artificial Neural Network (ANN) and Adaptive Neuro Fuzzy Inference System (ANFIS) Tools

Abstract: Lately, artificial neural network (ANN) and adaptive neuro-fuzzy inference system (ANFIS) models have been recognized as potential and good tools for mathematical modeling of complex and nonlinear behavior of specific wear rate (SWR) of composite materials. In this study, modeling and prediction of specific wear rate of polytetraflouroethylene (PTFE) composites using FFNN and ANFIS models were examined. The performances of the models were compared with conventional multilinear regression (MLR) model. To establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The researchers employed a hybrid approach, specifically the integration of genetic algorithms with ANFIS, referred to as GA-ANFIS, in order to forecast the wear characteristics of 3D printed composites by considering the printing factors. The wear rate of polytetrafluoroethylene (PTFE) composites was assessed by Ibrahim et al [44], who took into account many aspects like the weight fraction of reinforcement, the density of the composite, and the distance over which sliding occurred. Three prediction models were employed in the study, wherein the performance of a multilinear regression model was compared with that of an artificial neural network and an adaptive network-based fuzzy inference system.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers employed a hybrid approach, specifically the integration of genetic algorithms with ANFIS, referred to as GA-ANFIS, in order to forecast the wear characteristics of 3D printed composites by considering the printing factors. The wear rate of polytetrafluoroethylene (PTFE) composites was assessed by Ibrahim et al [44], who took into account many aspects like the weight fraction of reinforcement, the density of the composite, and the distance over which sliding occurred. Three prediction models were employed in the study, wherein the performance of a multilinear regression model was compared with that of an artificial neural network and an adaptive network-based fuzzy inference system.…”
Section: Introductionmentioning
confidence: 99%
“…They employed a combination of genetic algorithm and ANFIS, called GA-ANFIS, to anticipate how well the 3D-printed composite would perform in terms of wear based on the printing parameters used. Ibrahim et al [ 41 ] evaluated the wear rate of polytetrafluoroethylene composites through different factors, including reinforcement weight fraction, composite density, and sliding distance, using three prediction models. They compared the multilinear regression model’s performance with an artificial neural network and an adaptive network-based fuzzy inference system and found that the multilinear regression model outperformed the others with an accuracy of 97.4%.…”
Section: Introductionmentioning
confidence: 99%
“…ANFIS is considered a superior option for estimating input–output relationships in nonlinear situations [ 27 ], which is particularly relevant regarding parameters that affect 3D-printing technology. Ibrahim et al [ 28 ] aimed to predict the rate at which polytetrafluoroethylene composites wear due to factors such as the reinforcement weight fraction, the density of the composite, and the sliding distance. They compared the predictions made by three models: one based on multilinear regression, another on a feed-forward neural network, and a third on ANFIS.…”
Section: Introductionmentioning
confidence: 99%